HBR guide to finance basics for managers (Boston, Mass., 2012)
This book presents 13 articles to help managers understand finance basics, including speaking the language of finance by understanding financial statements and the laws of business; comparing a firm's financials with rivals'; using assets efficiently; examining vulnerability to industry downturns; shifting a unit's focus from revenues to profits; using financial data to defend budget requests; avoiding running out of cash and going out of business; keeping costs from killing the bottom line; investing smartly through cost-benefit analysis; selling ideas with return on investment; and avoiding relying too much on numbers.
Keywords: Business enterprises,Financial statements,Doanh nghiệp kinh doanh,Báo cáo tài chính; Finance,Tài chính